(untitled) (Scientific journal of the Fergana State University, 2025)
This article covers information about the development of national and mass sports in Uzbekistan in 1991-2005 on the basis of scientific, historical literature and sources. Also, according to the forgetful folk lifestyle, profession, labor character, feedback on a number of National Games related to agriculture, livestock farming, folk crafts, celebrations and weddings were drawn into the scope of research.